ANALISIS KEANDALAN METODE ANALISA FREKUENSI DAN INTENSITAS HUJAN BERDASARKAN DATA CURAH HUJAN KLIMATOLOGI BANJARBARU - Ahdianoor Fahraini; Achmad Rusdiansyah (Jurnal Teknologi Berkelanjutan, 2020)
Preventive measures that can be taken to prevent flooding when high rainfall discharge occurs, especially in the Banjarbaru area, is to plan water structures starting with rainfall analysis, especially rainfall frequency analysis to obtain planned rainfall and rainfall intensity. Data processing is carried out with daily maximum rainfall data of 30 years. Divided into 3 databases, the number of data is 10 years (data no. 1-10), the number of data is 15 years (data no. 1-15), and the number of data is 20 years (data no. 1-20). Each database calculates the planned rainfall for a return period of 2-20 years, the results of which are compared with the rainfall data from field measurements at the Banjarbaru Climatology Station. Next, analyze the accuracy of the rainfall intensity method by referring to the results of the previously analyzed rainfall plans. The formula to determine the accuracy of the rainfall frequency and intensity method uses the Peak-Weight Root Mean Square Error test, namely by taking the smallest deviation ratio value. Based on the Statistical Parameters test, the ChiSquare test and the Smirnov-Kolmogorov test get the Normal distribution analysis, but based on the comparison analysis the smallest deviation gets the Gumbel distribution. Rain intensity analysis with the smallest deviation test gets the Sherman formula. It is suggested that rainfall data with the same characteristics can use rainfall analyzes based on the Gumbel distribution and Sherman's formula for water building plans.